Tipe, Lingkungan dan Sejarah Diagenesis Batugamping Buliide Gorontalo Berdasarkan Analisis Petrografi (Jurnal Geomine, 2019)
The geological distribution of limestone in the central part of the Limboto Basin is an attraction for research on the type, environment, and history of limestone diagenesis processes. The study focused on the Buliide Region of Gorontalo City, which is in the southern part of Lake Limboto. This research became interesting because it was the first time it was done. The purpose of this study is three, namely to know the type of diagenesis, diagenesis environment and the history of the diagenesis process of Buliide limestone. The three objectives of the study will be achieved through two research methods, namely field surveys in the form of petrological analysis and laboratory analysis in the form of petrography analysis. The results showed the name Buliide limestone was coralline floatstone. There are five types of diagenesis processes, namely cementation, dissolution, replacement, micritization, and recrystallization. The diagenesis environment of Buliide limestone consists of the marine phreatic zone, vadose zone, and freshwater phreatic zone. The history of the diagenesis process of Buliide limestone can be divided into three stages, namely, the first stage occurs in the marine phreatic zone, the second stage of the freshwater phreatic zone and the third stage of the vadose zone with different diagenesis types.